2011
DOI: 10.1021/la103213n
|View full text |Cite
|
Sign up to set email alerts
|

Microstructured Silicone Substrate for Printable and Stretchable Metallic Films

Abstract: ABSTRACT:Stretchable electronics (i.e., hybrid inorganic or organic circuits integrated on elastomeric substrates) rely on elastic wiring. We present a technique for fabricating reversibly stretchable metallic films by printing silver-based ink onto microstructured silicone substrates. The wetting and pinning of the ink on the elastomer surface is adjusted and optimized by varying the geometry of micropillar arrays patterned on the silicone substrate. The resulting films exhibit high electrical conductivity (∼… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 25 publications
3
45
0
Order By: Relevance
“…Unfortunately, elastomeric substrates normally possess low melting points and high hydrophobicity, complicating fabrication processes based on lithography or inkjet printing. Accordingly, modifications in the fabrication techniques [88][89][90] , material substitutions 14,91 , and alternative designs 92,93 have been developed, eventually resulting in flexible soft substrates with improved stretchability and electrical conductivity. Another interesting alternative to all these fabrication techniques is the age-old fabrication process, that is, weaving.…”
Section: Sensor Fabricationmentioning
confidence: 99%
“…Unfortunately, elastomeric substrates normally possess low melting points and high hydrophobicity, complicating fabrication processes based on lithography or inkjet printing. Accordingly, modifications in the fabrication techniques [88][89][90] , material substitutions 14,91 , and alternative designs 92,93 have been developed, eventually resulting in flexible soft substrates with improved stretchability and electrical conductivity. Another interesting alternative to all these fabrication techniques is the age-old fabrication process, that is, weaving.…”
Section: Sensor Fabricationmentioning
confidence: 99%
“…This is especially problematic with silicones, which have a very low surface energy and present highly hydrophobic surfaces. Different surface treatments (plasma activation, UV exposure) can help to temporarily increase the surface energy, and Robinson et al have recently demonstrated how the wetting of a silicone substrate by a solvent-based ink can be improved by structuring the silicone substrate with micropillars [45]. The ink's evaporation rate must be controlled so as to avoid the "coffee stain" effect, which is caused by the motion of the ink's solid content to the periphery of the droplet, leading to a non-uniform coating once the layer is dry.…”
Section: Printing Techniquesmentioning
confidence: 99%
“…The absolute resistance increased by a factor 2.75 when stretched to 10% over 1000 cycles. Robinson et al 10 has shown that highly conductive lines can be produced by printing silver ink onto a micro-structured silicone substrate. The print lines were shown to have a resistance of 140 Ω for a 5mm long conductor with a width of 210 µm, a sheet resistance of approximately 5.9 Ω/□.…”
Section: Introductionmentioning
confidence: 99%